(untitled) (Research, Society and Development, 2023)
The present work presents the study of wind mapping in the state of Alagoas, northeastern Brazil, using the mesoscale model Weather Research Forecast (WRF), version (4.1.2), and approximations of atmospheric stability and terrain slope. The simulations were run daily for a period of 8 years (2007 - 2015), with a horizontal resolution of 5 km and a resolution refinement to 250 meters. They were statistically validated with data from 5 surface anemometric stations located in the following cities: Água Branca (hinterland), Girau do Ponciano (wild), Palmeira dos Índios (wild), Maragogi (coast) and Roteiro (coast). The order of magnitude and similar wind pattern results for the 5km and 250m resolutions indicate good representation by the WRF atmospheric model, as well as validating the proposed downscaling method. Being the moderate correlation indices, BIAS between -1.89 to 1.76 m/s and REQM between 1.94 to 3.82 m/s for wind speed and predominant wind direction varying between East/Southeast. The spatial comparison of the results with simulations of the WAsP model reinforces that the inclusion of atmospheric stability and slope made it possible to represent with greater clarity the effect of topography and surface roughness, which is crucial for reducing the cascade of uncertainties in the wind energy system. The refinement of the output of the WRF model highlighted the promising areas for wind use in the mountainous regions of the cities of Água Branca and Palmeira dos Índios, with annual intensity above 8m/s for 100m of height.